Adenosine Receptor-Mediated Cardioprotection—Current Limitations and Future Directions - Lasley, Robert D. (Frontiers in Pharmacology, 2018)
Since the seminal reports of adenosine receptor-mediated cardioprotection in the early 1990s, there have been a multitude of such reports in various species and preparations. Original observations of the beneficial effects of A1 receptor agonists have been followed up with numerous reports also implicating A2A, A3, and most recently A2B, receptor agonists as cardioprotective agents. Although adenosine has been approved for clinical use in the United States for the treatment of supraventricular tachycardia and coronary artery imaging, and the selective A2A agonist, regadenoson, for the latter, clinical use of adenosine receptor agonists for protecting the ischemic heart has not advanced beyond early trials. An examination of the literature indicates that existing experimental studies have several limitations in terms of clinical relevance, as well as lacking incorporation of recent new insights into adenosine receptor signaling. Such deficiencies include the lack of experimental studies in models that most closely mimic human cardiovascular disease. In addition, there have been very few studies in chronic models of myocardial ischemia, where limiting myocardial remodeling and heart failure, not reduction of infarct size, are the primary endpoints. Despite an increasing number of reports of the beneficial effects of adenosine receptor antagonists, not agonists, in chronic diseases, this idea has not been well-studied in experimental myocardial ischemia. There have also been few studies examining adenosine receptor subtype interactions as well as receptor heterodimerization. The purpose of this Perspective article is to discuss these deficiencies to highlight future directions of research in the field of adenosine receptor-mediated protection